The Implementation of Service Quality, Selling Prices, and Marketing Strategy for Customer Loyalty of PT. Indonesian Telecommunication (Indihome’s Case Study) - Andrian, Andrian; Triatmanto, Boge; Sugito, Pudjo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine whether service quality, selling price, and marketing strategy had an effect on customer loyalty, especially in the field of services. The research was conducted using a quantitative descriptive method. The location of this research was carried out at the Telkom Regional Operation Center 2 (ROC-2) Office, Central Jakarta. In this case the determination of the number of respondents using the Hair’s technique with total respondents in this study amounted to 75 customers who represent Indihome and Telkomsel users in Regional 2. Data collection methods used observation techniques and questionnaires. This research uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis test, hyphotesis test, and coefficient of determination test. The results showed that the service quality and selling price partially had no significant effect on customer loyalty, but the marketing strategy partially had a significant effect on customer loyalty. Based on the F test, the research results obtained are service quality, selling price, and marketing strategy simultaneously have a significant effect on customer loyalty.